Saskia Pronk-Tiethoff: The Germanic Loanwords in Proto-Slavic (= Leiden Studies in Indo-European 20) - Holzer, Georg (Slavia Centralis, 2020)
V prispevku je predstavljena knjiga The Germanic Loanwords in Proto-Slavic, ki je izšla leta 2013.